CLASSROOM ACTION RESEARCH TRAINING TO REALIZE TEACHER PROFESSIONALISM AT PRIMARY SCHOOL STATE 60 BUTON DISTRICT - Dahniar, Nur; Lely Nurmaya G, Andi; Musafir, Muhammad; Nurul Haq, Sitti; Regina, Reni (LPPM Univ. Ibn Khaldun Bogor, 2023)
The goal of this community activity is to encourage teachers in the 60 Buton state elementary education unit, which is located in East Lambusango Village, Kapontori District, Buton Regency, to increase their understanding about classroom action research and to realize professionalism. This activity method involves giving presentations, engaging in question-and-answer sessions, taking direction on creating classroom action research proposals, and getting mentoring on proposal preparation. The event took place in public room of the elementary school state 60 Buton. The program's outcomes demonstrate that, in general, the execution of training activities up to mentoring goes without a hitch. Through the use of draft proposals created by teachers who participated in the training, it was determined that the training activities had increased the knowledge of teachers on classroom action research. Additionally, the response from the participants was quite encouraging; they appeared to be very passionate about taking part in the training session, and they expressed a wish that this activity would continue on a constant schedule.